Tribological behavior and mechanism of a magnetic conductive brake pair under action of alternating magnetic field. (March 2019) - Bao, Jiusheng; Huang, Shan; Liu, Yang; Ge, Shirong; Yin, Yan; Liu, Tonggang
Abstract: Tribological experiments of a brake pair consisting of magnetic conductive organic friction pad and HT250 disc were conducted on a test bench of disc brake. SEM and EDS were used to reveal influence mechanisms. Results showed that both magnetic induction intensity and frequency have important influences on tribological performance. Friction temperature increases slightly with increasing of magnetic induction intensity. Debris is gradually refined and oxidation reaction becomes intensified, which promotes formation of friction layer on worn surface. Braking torque is then increased and braking process becomes more stable. Friction temperature increases greatly with increasing of magnetic field frequency. Increased magnetic frequency could improve wear resistance, but once frequency reaches a high enough value, dislocations aggregates and wear resistance declines. Highlights: Tribological experiments of brake pair with magnetic organic pad and HT250 disc were conducted on test bench of disc brake. The SEM and EDS were used to reveal influence mechanism of magnetic field on braking frictional performance of brake pair. Both magnetic induction intensity and magnetic field frequency have important influences on tribological performance. The research is believed valuable for improvement and controlling of braking performance based on magnetic field techniques.